2015
DOI: 10.5539/ass.v11n16p62
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and Delinquent Behavior among High Risk Youth in Malaysia

Abstract: Currently there is an alarming increase on youth involved in delinquency and criminal action in urban and sub urban areas of Malaysia. This paper aimed to measure the level of aggressive and delinquent behaviour, identify the most common delinquent behaviours, and examine the associations of aggressive and delinquent behaviour with demographic factors and individual characteristics among a sample of high risk Malaysian youth. The data used in this paper was obtained from a larger study designed to identify pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
1
15
0
2
Order By: Relevance
“…Thus, this finding supported the previous studies from Ali. K [13], Haslinda [2], Pit-Wan Pung [8] and Shahabudin [7]. The future direction on policy implementation to solve this issue must prioritize the role of parents in family institution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this finding supported the previous studies from Ali. K [13], Haslinda [2], Pit-Wan Pung [8] and Shahabudin [7]. The future direction on policy implementation to solve this issue must prioritize the role of parents in family institution.…”
Section: Resultsmentioning
confidence: 99%
“…using drugs, damaging public properties, hitting or physical assaulting others, driving without a license, carrying weapon, drinking alcohol, engaging in premarital sex, etc.) [2]. Meanwhile youth or delinquency refers to the participation in illegal behaviour by young people under the statutory age of majority which in most countries is 19 years old [3].…”
Section: Delinquent Behavior: Issues and Challenges A Delinquent Behmentioning
confidence: 99%
“…Crime is thought to be a complex phenomenon that has various cumulative effects on the aspects of finance and psychology such as the loss of justice, insurance, security, property, and victimization (Andresen & Jenion, 2008). At present there is an alarming growth on youth involved in delinquency and https: //dx.doi.org/10.15405/epsbs.2018.12.03.52 Corresponding Author: Fazilah Mohd Othman Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 543 criminal behaviour in urban and sub urban areas of Malaysia (Abdullah et al, 2015). Past research have found that students who were affected and became victims of crime demonstrate poor academic achievement (MacMillan & Hagan, 2004;Wei & Williams, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, in line with the existing literature, the present study indicated that adolescence with family support issues were more likely to engage with risky behaviour. Moreover, according to by Abdullah, Ortega, Ahmad & Ghazali (2015) in their study, family socioeconomic status can also influence the development of risky behaviour in adolescents. This may be construed as low socioeconomic status can contribute to risk behaviour.…”
Section: Findings and Discussionmentioning
confidence: 99%